Produksi Tempe Kedelai dalam Perspektif Ekonomi Islam - Ana Nurhayati; Seri Yanti Siagian; Sai'in Sai'in (STAI Auliaurrasyidin Tembilahan, 2021)
The production of soybean tempeh is a business run by the owner of soy tempeh in Tembilahan city using fermented soybean as raw material and has good nutritional value for human health. This study aims to determine the production of soybean tempeh in the city of Tembilahan and to determine the production of soybean tempeh from an Islamic economic perspective. This type of research is qualitative research. The subject of this research is the owner of the soybean tempe production site in the city of Tembilahan, totaling 4 tempe owners. While the object of research is the production of soybean tempe in the city of Tembilahan in the perspective of Islamic economics. The data was collected by interview, observation and documentation. The conclusion of this research is the soybean tempeh production has not fully carried out the production process according to the perspective of Islamic economics, this can be seen from the discrepancy in the application of work in fields that are permitted by Allah, namely in one of the production sites, namely the application of the system. wages to workers and reduction of scales that have been regulated in Surah Al-Hadid verse 25 and Al-Isra verse 35